Low-Dose Heparin and Deep-Vein Thrombosis after Total Hip Replacement - Mannucci, P. M; Citterio, Luisa E.; Panajotopoulos, N (Thrombosis and Haemostasis, 1976)
The effect of subcutaneous low-dose heparin on postoperative deep-vein thrombosis (D. V. T.) (diagnosed by the 125I-labelled fibrinogen test) has been investigated in a trial of 143 patients undergoing the operation of total hip replacement. Two randomized studies were carried out: in one the scanning for D.V.T. was carried out daily for 7 days post operatively and in the other for 15 days. In both, the incidence of D.V.T. was significantly lower in the heparin-treated patients (P<0.005). Bilateral D.V.T. was also prevented (P<0.05), through the extension of D.V.T. to the distal veins of the thigh was not significantly reduced. Heparin treatment was, however, followed by a higher incidence of severe postoperative bleeding (P< 0.02) and wound haematoma formation (P< 0.005), and the postoperative haemoglobin was significantly lower than in the control group (P<0.005). A higher number of transfused blood units was also needed by the heparin treated patients (P<0.001).